Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Budaya Organisasi Terhadap Kinerja Guru Pada SMK Negeri 1 Kota Bima: The Influence of The Principals Leadership Style and Organizational Culture on Teacher Performance at State Vocational School 1, Bima City - Fiqri Hadiputra, Yasril; Irawan, Ikbal; Aprianti, Kartin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the influence of the principal's leadership style and organizational culture on teacher performance at SMK Negeri 1 Kota Bima. The research instrument used a Likert scale questionnaire. The population was 93 respondents with a sample of 40 respondents using a purposive sampling technique. Data collection techniques used observation, questionnaires, and literature studies. Analysis used multiple linear regression. The results of the study indicate that both leadership style and organizational culture have a significant influence on teacher performance at SMK Negeri 1 Kota Bima, partially and simultaneously.